El perfil del gestor deportivo municipal brasileño (The profile of the brazilian municipal sports manager) - Bavaresco, Gustavo; Camargo, Philipe; Castro, Suélen Barboza Eiras de; Souza, João Victor Moretti; Marinho Mezzadri, Fernando (Retos, 2024)
El presente estudio tuvo como objetivo identificar el perfil del gestor deportivo público que trabaja a nivel municipal en diferentes estados brasileños. Se consideraron como muestra las regiones Nordeste, Centro-Oeste, Sudeste y Sur, a través de los estados de Bahia, Ceará, Espírito Santo, Minas Gerais, Mato Grosso do Sul, Paraná, Rio Grande do Norte, Santa Catarina y Sergipe, para un total de 1.955 municipios en esta investigación. El análisis se basó en los datos relativos al eje "Recursos Humanos" del instrumento Gestión del Deporte en Estados y Municipios (GEEM). Los resultados mostraron predominio masculino, diferencias en Raza; Edad; Escolaridad; Nivel de escolaridad; y Remuneración; tanto para cada estado como para cada región del país. Se concluye que es necesaria la formación académica y profesional de gestores públicos en el área de la educación física, combinada con la gestión deportiva, para que las políticas públicas sean más eficaces, así como la continuidad de los programas de servicio público independientemente de la región. Palabra clave: Gestión, Gestión Deportiva, Política Pública, Gestor Deportivo, Perfiles de Gestor. Abstract. This study aims to identify the profile of the public sports manager working at the municipal level in different Brazilian states. The Northeast, Centre-West, Southeast, and South regions were considered as the sample, through the states of Bahia, Ceará, Espírito Santo, Minas Gerais, Mato Grosso do Sul, Paraná, Rio Grande do Norte, Santa Catarina, and Sergipe, for a total of 1.955 municipalities in this research. The analysis was based on data relating to the "Human Resources" axis of the Sports Management in States and Municipalities (GEEM) instrument. The results showed a predominance of males, differences in Race; Age; Schooling; Level of School; Remuneration, both for each state and each region of the country. The conclusion is that there is a need for the academic and professional training for public managers in the field of physical education, combined with sports management, in order to make public policies more effective, as well as the continuation of public service programmes independent of the region. Keywords: Management, Sport Management, Public Policy, Sports Manager, Profile Manager.